The Effect of Job Description and Workload on Employee Performance - Ekhsan, Muhamad; Syariefa, Laditry Susthia; Astuti, Dwi; Badrianto, Yuan; Young, Felina C. (Proceeding International Pelita Bangsa, 2023)
This research aims to analyze the influence of job description and workload on employee performance in a pharmaceutical company in Cikarang. The study emphasizes the importance of human resources in an organization and how a workload that does not align with the job description can affect employee satisfaction and performance. Initial observations conducted in one of the pharmaceutical company's departments in Cikarang indicate that the workload does not match the job description, leading to dissatisfaction and suboptimal performance. Job description is described as a crucial factor in an organization to acquire quality and productive employees. An imbalanced workload can result in fatigue and various negative impacts on employees. Employee performance is interpreted as the qualitative and quantitative output achieved by an employee in line with their responsibilities. Employee performance is influenced by the job description and workload they receive. The research methodology employed is quantitative, utilizing a questionnaire for data collection. The analysis is conducted using Algorithm R Square and Bootstrapping Path Coefficients analysis in SmartPLS. The implications of the research include steps to enhance the quality of job descriptions and manage workloads, along with recommendations for workload equalization and continuous monitoring.